2010
DOI: 10.1109/tcsi.2009.2037850
|View full text |Cite
|
Sign up to set email alerts
|

A 4 GHz Non-Resonant Clock Driver With Inductor-Assisted Energy Return to Power Grid

Abstract: Abstract-Power consumption of a multi-GHz local clock driver is reduced by returning energy stored in the clock-tree load capacitance back to the on-chip power-distribution grid. We call this type of return energy recycling. To achieve a nearly square clock waveform, the energy is transferred in a non-resonant way using an on-chip inductor in a configuration resembling a full-bridge DC-DC converter. A zero-voltage switching technique is implemented in the clock driver to reduce dynamic power loss associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Increasing the WL voltage stepwise is effective for reducing energy dissipation. As for the clock driver, a charge recycling circuit with an inductor has been proposed and its effectiveness was confirmed by experiment [17]- [20]. As for SAR (successive approximation register) analog-to-digital converters [14], it has been shown that stepwise charging is effective for reducing energy dissipation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increasing the WL voltage stepwise is effective for reducing energy dissipation. As for the clock driver, a charge recycling circuit with an inductor has been proposed and its effectiveness was confirmed by experiment [17]- [20]. As for SAR (successive approximation register) analog-to-digital converters [14], it has been shown that stepwise charging is effective for reducing energy dissipation.…”
Section: Introductionmentioning
confidence: 95%
“…The voltage waveform is sinusoidal due to the resonance. For the LC nonresonant circuit, it has been reported that power consumption is reduced to 65% of the total at 4 GHz [20]. The voltage waveform is nearly square with fast edges.…”
Section: Features Of Stepwise Circuitmentioning
confidence: 99%
“…The required wide programmability is not feasible with classical analog solutions but can be achieved with digital signal processors (DSPs). Classical clocked DSPs have advanced through robust solutions but are still difficult to implement at very high clock rates, due to power requirements for clock generation and distribution [1], [2], EMI issues, and the need for an antialising filter. Further, such processors continue dissipating dynamic power even during lulls in the input, unless complex power management scenarios are adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The solution generally adopted is that of a closed-loop-with-active-compensation that is implemented by means of phase-locked loops (PLLs) and delay-locked loops (DLLs) [12], [13]. In this context, much effort has been devoted to reducing jitter and power [4], [14]- [21]. However, these techniques are also generally power-and area-hungry.…”
mentioning
confidence: 99%